Художественный стиль украшения поясов в Хазарии второй половины VIII – начала X вв. - Фонякова, Н.А. (Материалы по археологии, истории и этнографии Таврии, 1998)
The artistic style of decorating belts in Khazaria in the second half of the 8th - the beginning of the 10th centuries is under consideration in this article. According to the ECM computer programme of identifying images 2 groups of belts with specific features are singled out. One of them is associated with Turk forms of belts, the other one - with brackets for footwear, similar to the North-Caucasian ones.